2023
DOI: 10.3389/fnagi.2023.1213904
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain functional connectivity in vegetative state and minimally conscious state

Abstract: ObjectivesThe pathological mechanism for a disorder of consciousness (DoC) is still not fully understood. Based on traditional behavioral scales, there is a high rate of misdiagnosis for subtypes of DoC. We aimed to explore whether topological characterization may explain the pathological mechanisms of DoC and be effective in diagnosing the subtypes of DoC.MethodsUsing resting-state functional magnetic resonance imaging data, the weighted brain functional networks for normal control subjects and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In this context, increased inhibition and decreased excitatory output of the thalamus have been identified as a hallmark in DoC [124,125], with the highest relevance in the thalamofrontal connection [126,127]. Interestingly, a study revealed an increased degree of centrality of the thalamus in DoC patients compared to controls associating it to compensatory mechanisms and a reorganization of network structure [128]. This higher coupling and communication of the thalamus with other brain areas might explain the broadcasting of the local stimulation in the thalamus at the global level dynamics, as revealed in our results.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…In this context, increased inhibition and decreased excitatory output of the thalamus have been identified as a hallmark in DoC [124,125], with the highest relevance in the thalamofrontal connection [126,127]. Interestingly, a study revealed an increased degree of centrality of the thalamus in DoC patients compared to controls associating it to compensatory mechanisms and a reorganization of network structure [128]. This higher coupling and communication of the thalamus with other brain areas might explain the broadcasting of the local stimulation in the thalamus at the global level dynamics, as revealed in our results.…”
Section: Plos Computational Biologymentioning
confidence: 99%